Open-Circuit Fault Mitigation for Inverter-Driven Induction Motor Based on Closed-Loop Volt-per-Hertz - Mohammad Alathamneh; Haneen Ghanayem; R. M. Nelms; Ibrahim M. Allafi (Energies)
Presented in this paper is a mitigation technique for an open-circuit fault (OCF) in a closed-loop Volt-per-Hertz controlled three-phase induction motor. Conventional proportional–integral (PI) controllers have been found inadequate for maintaining stable motor performance during the fault and exhibit significant transient issues when transitioning from fault to normal operation. To address these limitations, a proportional–resonant (PR) control method and a proportional–integral–resonant (PIR) control method are proposed. The PIR controller enhances the traditional PI controller by integrating a resonant component, enabling effective performance during the fault and improving transient responses during pre-fault conditions. Experimental validation using a dSPACE DS1104 platform demonstrates that the PR and PIR control methods significantly improve motor performance compared to the PI method. The proposed approaches eliminate the need for fault detection, offering a simpler and cost-effective alternative for maintaining motor reliability and efficiency under fault conditions. These results underscore the potential of the proposed method as a robust solution for the fault scenarios in industrial applications.